Attitudes of Slovene paediatricians to end‐of‐life care. (29th October 2015) - Grosek, Stefan; Orazem, Miha; Kanic, Maja; Vidmar, Gaj; Groselj, Urh
Abstract : Aims: The aims of this study were to assess the attitudes of Slovene paediatricians to aspects of end‐of‐life (EOL) care and compare these attitudes between paediatric intensivists, paediatric specialists and paediatric residents. Methods: We performed a cross‐sectional survey, using a specifically designed 43‐item anonymous questionnaire. Results: We included 323 out of 586 Slovene paediatricians and residents, while 46.7% (151 of 323) of them responded to our questionnaire. More than half of intensivists (54.2%) had sought counsel from the Committee for Medical Ethics in the past as compared with 12.0% and 12.1% of specialists and residents, respectively ( P < 0.001). The decision to limit life‐sustaining treatment (LST) was found to be ethically acceptable in all groups of respondents. The highest level of agreement was found in residents (90.2%), followed by 83.3% among intensivists and 73.8% among specialists ( P = not statistically significant (NS)). Disagreement with termination of hydration was highest among residents (85%) and intensivists (79.2%) while it was lower among specialists (66.7%) ( P = NS). Patient's best interest, good clinical practice and patient's autonomous decision were graded as the top three aspects of the EOL care, while cost effectiveness and availability of patient's bed in intensive care were the least important. Conclusions: The decision to limit LST measures was found to be ethically acceptable for Slovene paediatricians. No major differences were found among paediatric intensivists, specialist paediatricians and paediatric residents in the attitudes towards the EOL care.